Biomass‐Derived Carbon Materials for Electrochemical Energy Storage - Bai, Yu‐Lin; Zhang, Chen‐Chen; Rong, Feng; Guo, Zhao‐Xia; Wang, Kai‐Xue (Chemistry : a European journal, 2024)
The environmental impact from the waste disposal has been widely concerned around the world. The conversion of wastes to useful resources is important for the sustainable society. As a typical family of wastes, biomass materials basically composed of collagen, protein and lignin are considered as useful resources for recycle and reuse. In recent years, the development of carbon material derived from biomasses, such as plants, crops, animals and their application in electrochemical energy storage have attracted extensive attention. Through the selection of the appropriate biomass, the optimization of the activation method and the control of the pyrolysis temperatures, carbon materials with desired features, such as high‐specific surface area, variable porous framework, and controllable heteroatom‐doping have been fabricated. Herein, this review summarized the preparation methods, morphologies, heteroatoms doping in the plant/animal‐derived carbonaceous materials, and their application as electrode materials for secondary batteries and supercapacitors, and as electrode support for lithium‐sulfur batteries. The challenges and prospects for the controllable synthesis and large‐scale application of biomass‐derived carbonaceous materials have also been outlooked. The design and preparation of biomass‐derived porous carbon materials in recent five years was summarized. These carbon materials were briefly catalogized into two types, plant‐derived and animal‐derived carbon materials. Heteroatoms doping was illustrated with an emphasis on single‐element doping and multi‐element doping, respectively. The advantages of these porous carbon materials applicated in electrochemical energy storage devices, such as LIBs, SIBs, PIBs, and SCs were reviewed. The remaining challenges and prospects in the field were outlined.